2022
DOI: 10.1038/s41419-022-05160-6
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative p53-overexpression in skeletal muscle induces cell death and fiber atrophy in rats

Abstract: The tumor suppressor p53 is thought to play a key role in the maintenance of cell size and homeostasis, but relatively little is known about its role in skeletal muscle. Based on its ability to suppress cell growth, we hypothesized that inhibiting the function of wild-type p53 through the overexpression of a dominant-negative p53 mutant (DDp53) could result in muscle fiber hypertrophy. To test this hypothesis, we electroporated adult rat tibialis anterior muscles with DDp53 and collected the tissue three weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
6
1
Order By: Relevance
“…This suggests that measuring MPS does not necessarily reflect net protein accrual, but rather the remodeling state of muscle. In agreement with this, it has been shown in rodents that MPS and associated anabolic signals can be increased in scenarios where overall muscle mass is lost rather than gained [74][75][76][77]. Indeed, pre-clinical and clinical studies suggest that the amount of muscle damage in response to RE might be more pronounced in older compared to younger individuals [56,78].…”
Section: Difference In Recovery From Resistance Exercise In Aged Musclesmentioning
confidence: 60%
“…This suggests that measuring MPS does not necessarily reflect net protein accrual, but rather the remodeling state of muscle. In agreement with this, it has been shown in rodents that MPS and associated anabolic signals can be increased in scenarios where overall muscle mass is lost rather than gained [74][75][76][77]. Indeed, pre-clinical and clinical studies suggest that the amount of muscle damage in response to RE might be more pronounced in older compared to younger individuals [56,78].…”
Section: Difference In Recovery From Resistance Exercise In Aged Musclesmentioning
confidence: 60%
“…2 ). How chronic stabilization of p53 negatively influences myofiber function is not clear, as the role of p53 in skeletal muscle has largely been investigated with loss-of-function studies [ 41 , 43 , 44 , 60 ]. Recent data suggests that in addition to its classically described role as a transcription factor, cytoplasmic p53 also plays important biological functions, including suppressing autophagy [ 61 ], mitochondrial permeability and production of reactive oxygen species [ 62 , 63 ], and modulation of Ca 2+ homeostasis between mitochondria and endoplasmic reticulum [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that p53 overexpression leads to the emergence of senescent traits and muscle atrophy [33,37], and muscle-specific p53-knockout (KO) mice were partially resistant to immobilization-induced skeletal muscle atrophy [33]. Conversely, muscle atrophy was induced in a p53 loss-offunction model created through the overexpression of dominant-negative p53 protein [38]. In an animal model of immobilization, the degree of muscle atrophy was found to be similar between muscle-specific p53-KO mice and wild-type mice [36], and aging-related muscle atrophy was not suppressed in the same KO mice described above [39].…”
Section: Discussionmentioning
confidence: 99%